Influence of solid solubility and twin crystals on the deformation mechanism of nano single crystal Cu/Al2Cu/Al interface Configuration: A molecular dynamics simulation - Hui Zhang; Aiqin Wang; Aiqiong Pan; Jingpei Xie (Journal of Materials Research and Technology)
This paper systematically investigates the tensile deformation behavior of copper-aluminum laminated composites with nano single crystal Cu/Al2Cu/Al interface configuration. using molecular dynamics (MD) simulation. The influence of solid solubility and twin crystals on the deformation behavior of copper-aluminum laminated composites with nano single crystal Cu/Al2Cu/Al interface structures was analyzed in-depth. Four interface models are established:no solid solubility and twin crystals model (NN-model), solid solubility model (SN-model), twin crystals model (TN-model), and solid solubility and twin crystals model (ST-model). A comparative analysis revealed that dislocation slip serves as the primary deformation mechanism in the aluminum layer, while twinning dominates in the copper layer. Additionally, the Al2Cu layer contributes to synergistic deformation. Solid solubility minimally affects the Young's modulus of the material and diminishes both ultimate tensile strength and plasticity. Conversely, twin crystals substantially enhance Young's modulus and plasticity but also reduce the ultimate tensile strength. These effects result from the interactions among solid solubility, twin crystals, heterogeneous interfaces, and dislocations. Consequently, thoughtful regulation and design of solid solubility and twin crystals can facilitate the fabrication of copper-aluminum laminated composites with optimal strength-toughness synergy.